PENDAMPINGAN BIMBINGAN BELAJAR SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN AKADEMIK ANAK USIA TK DAN SD DI DUSUN JADUGAN - Hafif Komarullah; Betty Handayani; Yatik Wasilah; Ismi Ulfatul Ilmiyah; Humairoh Humairoh (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service program aimed to improve the literacy and numeracy skills of kindergarten (TK) and elementary school (SD) children through community-based tutoring assistance in Jadugan Hamlet. The main problems addressed were the low levels of reading, writing, and arithmetic skills among children and the limited learning support outside formal schooling. The program employed a Participatory Action Research (PAR) approach consisting of the stages of problem diagnosis, participatory planning, action, observation, and reflection. The participants were 17 children, comprising 5 kindergarten students and 12 elementary school students. Data were collected through structured observation using a developmental checklist, brief interviews with parents, and documentation, and were analyzed using a qualitative descriptive approach supported by numerical data. The results indicated an improvement in children’s academic abilities, with the proportion of children categorized as developing increasing to 70.6% in reading, 64.7% in writing, and 76.5% in numeracy. In addition, 82.4% of the children demonstrated increased learning motivation and participation, while 76% of parents showed greater involvement in assisting their children’s learning at home. The program also fostered collective awareness within the community regarding the importance of children’s education. These findings suggest that community-based tutoring assistance using a PAR approach is effective in enhancing children’s academic skills and learning motivation while strengthening the role of families and communities in supporting sustainable education.